Answer:
one solution ⇒ 1st answer
Explanation:
* Lets explain how to solve the question
- The 1st equation is 6x + 3y = 12
- The 2nd equation is y = 2x + 4
- To solve the two equation substitute y in the 1st equation by the
2nd equation
∴ 6x + 3(2x + 4) = 12
- Multiply 3x by the bracket (2x + 4)
∴ 6x + 6x + 12 = 12
- Subtract 12 from both sides
∴ 12x = 0
- Divide both sides by 12
∴ x = 0
- Substitute the value of x in the 2nd equation
∴ y = 2(0) + 4
∴ y = 4
∴ The solution is (0 , 4)
* There is one solution for this system